1994
DOI: 10.1063/1.870465
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear surface waves in a plasma with a diffuse boundary

Abstract: The propagation of surface waves in a plasma with a diffuse boundary is considered. Three equations governing the evolution of the system are derived. If the excursion length of the electrons in the surface wave field is smaller than the width of the plasma–vacuum transition layer, it is found that typically the nonlinear density modifications in the boundary layer are more important than the previously investigated bulk nonlinearities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Two-dimensional (2D) nonlinear oscillations on plasma surfaces have unusual properties [1][2][3][4][5]. The interface dynamics is described by nonlinear Schrödinger equations (NSEs) that differ from the standard NSE and its modifications.…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…Two-dimensional (2D) nonlinear oscillations on plasma surfaces have unusual properties [1][2][3][4][5]. The interface dynamics is described by nonlinear Schrödinger equations (NSEs) that differ from the standard NSE and its modifications.…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…Also the velocity u can be arbitrarily chosen. Other improvements could be the consideration of moving or diffuse [2] boundaries. As discussed in Section IV, the model Eq.…”
Section: Discussionmentioning
confidence: 99%
“…The description of nonlinear plasma surface waves is a growing subfield in plasma physics [1,2]. Reasons for this research can be found in industrial applications [3], plasma microwave diagnostics [4], some aspects in laser fusion [5] and space plasma physics [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the linear approximation equations (11) and (13) Next, we shall solve the coupled equations (11) and (13) numerically.…”
mentioning
confidence: 99%
“…Equation(11) describes the influence of the Alfven wave field W, (corresponding to the velocity in the z direction) that essentially is localized around the resonance, on the surface wave field P], which determines Equation (13) describes the evolution of the Alfven wave field 'Ij', which is driven by the surface wave field P~. The two coupled equations…”
mentioning
confidence: 99%